Challenges for Methods of Teaching English Vocabulary to Non-native Students - Elmahdi, Omer Elsheikh Hago; Hezam, Abdulrahman Mokbel Mahyoub (Advances in Social Sciences Research Journal, 2020)
This study is meant to have a through argument about the main topic of this research, which is the challenges of teaching methods of English vocabulary to non-native students. The researchers try to introduce a conceptual coverage of certain areas that are relevant to English vocabulary teaching / learning. This conceptual coverage includes: the definition of the term vocabulary, kinds of vocabulary, the importance of vocabulary, general principles for successful vocabulary teaching, teaching vocabulary in the English as a foreign language (EFL) context is challenging, techniques of teaching vocabulary, and the need for teaching vocabulary. Among the qualitative methods the researchers chose the record keeping method. This method makes use of the already existing reliable documents and similar sources of information as the data source. This data can be used in a new research. The researchers have collected a number of relevant studies and quarrying critically and deeply in these studies to signal out the Challenges for Methods of Teaching English Vocabulary to Non-native Students. Qualitative data collection allows collecting data that is non-numeric and helps us to explore how decisions are made and provide a detailed insight. For reaching such conclusions the data that is collected should be holistic, rich and nuanced and findings to emerge through careful analysis. This is why the researchers have examined and collected many relevant references, case studies that deal with teaching vocabulary. To carry out this research the researchers have introduced certain questions and surveyed a huge number of previous studies after covering the relevant literature. Finally, the challenges that are critically obtained by the researchers are classified into three main categories. The first category, challenges related to students, the second one, challenges related to teachers, and the third one, challenges related to methods/ techniques/ strategies of teaching vocabulary.